THE UTTERANCES OF LEKGOTHOANE (MAKXOTHLO) AND THOSE OF THE APOSTLE PAUL (I CORINTHIANS 15: 55): AN INTERTEXTUAL READING - Mojalefa, M. J. (Literature and theology, 1999)
This article discusses the liberation of the oppressed Black people in South Africa from (a) sin (a theological perspective), and (b) apartheid (a political point of view, as manifested in the literature of Lekgothoane). This discussion is based on an investigation of the intertextuality of the poem written by Lekgothoane entitled Makvothlo1 and the utterance of the Apostle Paul in one of his Letters to the Corinthians2 in the New Testament.